24=(x*7)-(x*3)

Simple and best practice solution for 24=(x*7)-(x*3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 24=(x*7)-(x*3) equation:


Simplifying
24 = (x * 7) + -1(x * 3)

Reorder the terms for easier multiplication:
24 = (7x) + -1(x * 3)

Reorder the terms for easier multiplication:
24 = (7x) + -1(3x)

Remove parenthesis around (3x)
24 = (7x) + -1 * 3x

Multiply -1 * 3
24 = (7x) + -3x

Combine like terms: (7x) + -3x = 4x
24 = 4x

Solving
24 = 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
24 + -4x = 4x + -4x

Combine like terms: 4x + -4x = 0
24 + -4x = 0

Add '-24' to each side of the equation.
24 + -24 + -4x = 0 + -24

Combine like terms: 24 + -24 = 0
0 + -4x = 0 + -24
-4x = 0 + -24

Combine like terms: 0 + -24 = -24
-4x = -24

Divide each side by '-4'.
x = 6

Simplifying
x = 6

See similar equations:

| 10x+10y=2 | | 0.2x-2.9=2.9x+2.8 | | 1b+94a=24 | | e^1-5x=37 | | 2(x+6)-7= | | 8(7-1)=-24 | | 21=6g-9 | | 180=x(x-4)(x+9) | | (3c^2d^4)(-2c^2)= | | 0.25-2r=4 | | X(x-4)=4(x-5) | | 2x+46-3x= | | 2g+8=16 | | y+6=-9(x+10) | | 4x(10)2x-2=3x+4 | | a(n)=7+(n-1)(4) | | a(n)=7 | | -6+8(x-4)=12x+3-4x | | y+5=7(x+8) | | x(x+x)=4(4+5) | | .2x^2+12=3.4 | | 5(x+2)=12-3x | | x=1/2(110) | | ln(x+1)=x-0.8 | | Ln(x^2-25)=ln(-5x-1) | | 24x^2=180 | | Ln(x^2)=ln(-5x-1) | | 5(7n-4)+4=12+7n | | 2x+3z=2+5y | | 9n-8=-458 | | 9a-8=-260 | | 6n-5=271 |

Equations solver categories